Implementasi Metode Pottery Making Dan Pemasaran Digital Dalam Meningkatkan Produk Kreatif UMKM Tembikar Lestari Di Kecamatan Tanjung Morawa Deli Serdang Dalam Perspektif Ekonomi Islam - Rambe, Masnum; Sugianto, Sugianto; Syahbudi, Muhammad (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to: (1)knowing the application of pottery making in sustainable pottery (2) knowing the application of pottery making in increasing sustainable pottery production (3) the application of sustainable Pottery digital marketing (4) the application of digital marketing in the perspective of Islamic economics. The method used in this study is a qualitative method with a descriptive approach that is by observation, interviews and documentation with 6 sustainable Potters. Facebook Instagram, Google business, and Lestari Pottery implement digital marketing through social media, namely Facebook, Instagram and Google Business. Digital marketing done in sustainable pottery is still weak, especially on Facebook accounts and on Google Business. Sustainable pottery applies digital marketing according to the perspective of Islamic economics, which is associated with this business is well interconnected in improving creative products that are in accordance with the principles that have been in the Al-Qur'an. Based on the results of digital marketing, sustainable pottery is more active on social media, which is used mainly on Facebook and Google business, so that more often upload product photos and videos so that more information is shared faster in promoting sustainable pottery products.